Comparative Analysis of Performance Impact: Car Bumper Made from Empty Palm Fruit Bunch (EPFB) and Polypropylene (PP) - Halimudin, Nor Atiqah; Mahmudin, Rahmah; Marsi, Noraini (Progress in Engineering Application and Technology, 2025)
This study presents a comparative analysis of the performance impact of car bumpers made from empty palm fruit bunch (EPFB) composites versus those from conventional materials like polypropylene (PP). The use of EPFB fibers blended low-density polyethylene (LDPE) in polymer composites for production is low-cost and environmentally polluted, it is also lightweight when applied in car bumper applications. The bumper is a crucial safety component of the car that can absorb energy in a collision to ensure the passengers are safe. The research objectives were to evaluate the deformation, strain, and stress performance of EPFB composites and compare these properties to PP, identifying the most suitable EPFB composition as an alternative material for bumper application. ANSYS software is used in this research to examine the performance impact on car bumpers, which is by using features of static structural simulation. The results showed that the EPFB-LDPE 0.8% composites strike a good balance between flexibility and stiffness, performing a good alternative material as PP in stress while absorbing more energy. EPFB-LDPE composites may not be totally suited for direct usage as a bumper material in their current state due to significant deformation and strain, indicating probable shape retention and structural failure under heavy impact. While its ability to absorb stress is promising, the lack of stiffness complicates preserving structural integrity during crashes. Additionally, using EPFB composites supports sustainability by reusing agricultural waste and reducing reliance on non-renewable resources. In conclusion, the EPFB-LDPE 0.8% composite is a promising eco-friendly alternative to PP for car bumpers, combining reliable performance with environmental benefits and paving the way for greener innovations in the automotive industry.